2020
DOI: 10.1186/s13287-020-1556-7
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-NEAT1 from the competing endogenous RNA network promotes cardioprotective efficacy of mesenchymal stem cell-derived exosomes induced by macrophage migration inhibitory factor via the miR-142-3p/FOXO1 signaling pathway

Abstract: Aims: Extracellular vesicles, especially exosomes, have emerged as key mediators of intercellular communication with the potential to improve cardiac function as part of cell-based therapies. We previously demonstrated that the cardioprotective factor, macrophage migration inhibitory factor (MIF), had an optimizing effect on mesenchymal stem cells (MSCs). The aim of this study was to determine the protective function of exosomes derived from MIFpretreated MSCs in cardiomyocytes and to explore the underlying me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 65 publications
0
48
0
Order By: Relevance
“…Prior researches have recommended that lncRNA NEAT1 is a critical regulator in malignancy progression, and higher NEAT1 expression is connected with cell metastasis and invasion [19][20][21]. LncRNA NEAT1 has also been validated to be connected with sepsis-induced myocardial cell injury and the cardiomyocyte apoptosis induced by H 2 O 2 [22,23]. Interestingly, a study also found that NEAT1 affected cell viability and inflammatory reaction in epilepsy cell model induced by IL-1β [24].…”
Section: Discussionmentioning
confidence: 99%
“…Prior researches have recommended that lncRNA NEAT1 is a critical regulator in malignancy progression, and higher NEAT1 expression is connected with cell metastasis and invasion [19][20][21]. LncRNA NEAT1 has also been validated to be connected with sepsis-induced myocardial cell injury and the cardiomyocyte apoptosis induced by H 2 O 2 [22,23]. Interestingly, a study also found that NEAT1 affected cell viability and inflammatory reaction in epilepsy cell model induced by IL-1β [24].…”
Section: Discussionmentioning
confidence: 99%
“…The exosome quick extraction solution was added to the filtered solution at a 1:5 ratio and stored at 4 °C for at least 12 h. The precipitation (exosomes) was dissolved in PBS and stored at − 70 °C. The characterization of exosomes was carried out as previously reported [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that regaining MIF function attenuated cardiac injury [ 18 ]. Beneficial cardioprotective effects of exosomes derived from MSCs have also been reported in the pretreatment with MIF [ 19 ]. Given the potential therapeutic benefits of exosomes derived from MSCs pretreated with MIF (exosome MIF ), whether MIF pretreatment could affect the functions of exosomes in treating Dox-related cardiac senescence process needs to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations